2013
DOI: 10.1063/1.4775665
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial bonding and electronic structure of HfO2/GaSb interfaces: A first principles study

Abstract: The interfacial bonding and electronic structure of HfO 2 /GaSb interfaces has been investigated through first principles calculations. The calculated electronic structures of these interfaces reveal that some O-rich interfaces are semiconducting interfaces without any gap states. In contrast, for the interfaces with lower interfacial O content, gap states appear in the GaSb band gap, close to the conduction band. The valence band offsets are found to vary from 2.2 eV to 3.6 eV, depending on the interfacial O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…17 A detailed theoretical understanding of the origin of gap states of GaAs/HfO 2 and GaSb/HfO 2 interfaces and their possible passivation have also been studied previously. 6,18 The interface states are mainly due to interfacial defects (atoms with mismached valance charge or bond configuration) rather than due to intrinsic gap states like the metal induced gap states (MIGS). 19 However, a detailed theoretical study on the InP/HfO 2 interface, to identify the origin of the defects is not yet available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A detailed theoretical understanding of the origin of gap states of GaAs/HfO 2 and GaSb/HfO 2 interfaces and their possible passivation have also been studied previously. 6,18 The interface states are mainly due to interfacial defects (atoms with mismached valance charge or bond configuration) rather than due to intrinsic gap states like the metal induced gap states (MIGS). 19 However, a detailed theoretical study on the InP/HfO 2 interface, to identify the origin of the defects is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of the atomic and electronic structrures of this III-V/High-r interface provides insight on the origin of the interface defect states. [18][19][20][21][22] In this paper, an investigation of the origin of interface gap states of an ideal InP(001)/HfO2(001) interface and its dependence on the amount of interfacial oxygen concentration are presented. In addition, we also explain the effects of interfacial indium and phosphorous contents on the interfacial bonding, band offsets, and the thermodynamic stability of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…2 Gallium antimonide (GaSb) has attracted an increasing interest as for the channel material of future MOS transistors, in particular, due to a superior mobility of holes in GaSb. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The GaSb oxidation at the insulator interfaces such as atomiclayer-deposited (ALD) Al 2 O 3 /GaSb and HfO 2 /GaSb has been found to cause various oxidation states of GaSb including Ga 2 O, Ga 2 O 3 , Sb 2 O 3 , and/or Sb 2 O 5 according to x-ray photoelectron spectroscopy (XPS) measurements. 10,18 By obtaining interrelationship between the interfacial chemistry from, for example, XPS measurements and capacitance-voltage (C-V) characterization of the same interfaces, the effects of the oxidation states on the electrical properties of the interfaces have been clarified: it is interesting that neither Ga 2 O 3 -nor Sb 2 O 3type interface phase is necessarily harmful to the electrical performance.…”
mentioning
confidence: 99%
“…10 In fact, it was recently been demonstrated that for HfO 2 /GaSb interfaces, gallium (Ga) dangling bonds and Sb-Sb antibonding states are located inside the GaSb conduction band, which is in contrast to the well-studied high-j/GaAs in which Fermi level pinning is attributed to presence of Ga dangling bonds and As-As dimers. 11,12 Furthermore, higher interfacial oxide content is found to be beneficial in reducing the gap states. 12 A second challenge arises from the density of states (DOS) mismatch between the conduction band and the valence band.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Furthermore, higher interfacial oxide content is found to be beneficial in reducing the gap states. 12 A second challenge arises from the density of states (DOS) mismatch between the conduction band and the valence band. In n þ heavily doped source region of p-channel III-V TFETs, the Fermi level is degenerate and located far away from the conduction band edge, thereby preventing efficient energy filtering of conduction band holes as they tunnel from conduction band states into the valence band states in the channel.…”
Section: Introductionmentioning
confidence: 99%